2022
DOI: 10.3390/cancers14112600
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-Modulated Radiotherapy (IMRT) following Conservative Surgery of the Supraglottic Region: Impact on Functional Outcomes

Abstract: The aim of the present study was to investigate the role of intensity-modulated radiotherapy (IMRT) on the toxicity profile of patients treated with conservative surgery (CS) of the supraglottic (SG) region. Data on patients treated with CS and postoperative radiotherapy (PORT)-IMRT were prospectively collected. Results. In total, 20 patients were analyzed. Of these, six patients (35%) required the positioning of a temporary tracheostomy. The functional larynx preservation rate was 95%. Females had a higher ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In a previously published study by our group 20 , the toxicity profile of 20 patients treated with IMRT was compared to that of 32 patients who received 3D-CRT. Compared to the 3D-CRT group, patients treated with IMRT experienced a lower rate of permanent aspiration/pneumonia (6% vs 0%, respectively), laryngeal stenosis requiring endoscopic dilatation (21% vs 15%, respectively), laryngeal necrosis (6% vs 0%, respectively), and permanent tracheostomy (12.5% vs 5%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In a previously published study by our group 20 , the toxicity profile of 20 patients treated with IMRT was compared to that of 32 patients who received 3D-CRT. Compared to the 3D-CRT group, patients treated with IMRT experienced a lower rate of permanent aspiration/pneumonia (6% vs 0%, respectively), laryngeal stenosis requiring endoscopic dilatation (21% vs 15%, respectively), laryngeal necrosis (6% vs 0%, respectively), and permanent tracheostomy (12.5% vs 5%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, supraglottic cancers amenable to CHP are more likely to demonstrate cervical lymph node involvement that would require postoperative radiation 27 . Administering radiation after SCPL is typically not advised, as it further exacerbates the higher rates of dysphagia and respiratory dysfunction associated with surgical resection of the supraglottic region 28 . Thus, the disproportionate usage of CHEP over CHP reconstruction may also represent a sample selection bias in favor of disease that does not require postoperative radiation.…”
Section: Discussionmentioning
confidence: 99%
“…27 Administering radiation after SCPL is typically not advised, as it further exacerbates the higher rates of dysphagia and respiratory dysfunction associated with surgical resection of the supraglottic region. 28 Thus, the disproportionate usage of CHEP over CHP reconstruction may also represent a sample selection bias in favor of disease that does not require postoperative radiation. The frequencies of CHEP and CHP reconstructions observed in this review are similar to those reported in Europe.…”
Section: Primary Objective: Oncologic Outcomes Following Supracricoid...mentioning
confidence: 99%